Structure and phase engineering of 2D transition metal chalcogenides - Tang, Bijun (Nanyang Technological University, 2021)
As an indispensable member of the two-dimensional (2D) family as well as a perfect complement to graphene, 2D transition metal chalcogenides (TMCs) have long been the center of research attention, attributed to their large spectrum of fascinating properties along with the various crystal structures. In parallel with the discovery of new candidate materials and exploration of their unique characteristics, engineering the 2D TMCs into designated structures and phases are also of great importance for meeting the requirement for different applications. This thesis focuses on the structure and phase engineering of 2D TMCs to tune their physicochemical properties. Four strategies are adopted to tune the properties of 2D TMCs by fabricating them into desired structures, architectures, or defined phases: construction of heterostructure, alloying, phase-selective growth, and dimension tuning. Moreover, this thesis also describes and validates the feasibility and potential of introducing ML to guide the synthesis and engineering of 2D TMCs.